Experimental Investigation of a PV-Powered Blower-Assisted Solar Still: Effects of Seawater Volume on Evaporation–Condensation Efficiency - Zaenal Ikhsan Abdullah; Ridwan Ridwan; Iwan Setyawan; Hamzah Ali Nashirudin; Deni Haryadi (International Journal of Engineering Continuity, 2026)
This study investigates the performance of a photovoltaic-assisted solar still integrated with a blower system to enhance desalination efficiency. The system was experimentally evaluated to examine the influence of thermal parameters on freshwater productivity and system efficiency. The results show that distilled water production ranges from 0.35 to 0.55 L/day, with an efficiency of 7–8%. The highest productivity occurred at an evaporator temperature of 47.6–48 °C, confirming temperature as the dominant parameter. The PV-powered blower increased the temperature gradient between the evaporator and condenser by promoting forced air circulation, improving heat and mass transfer. However, the system performance remains within the conventional range, indicating that heat losses and limited condensation efficiency are key constraints. This study demonstrates the potential of photovoltaic-powered, blower-assisted solar stills to enhance evaporation–condensation processes and provides a baseline for further system optimization.